Recovering Quality of Life (ReQoL): a new generic self-reported outcome measure for use with people experiencing mental health difficulties†. (January 2018) - Keetharuth, Anju Devianee; Brazier, John; Connell, Janice; Bjorner, Jakob Bue; Carlton, Jill; Taylor Buck, Elizabeth; Ricketts, Thomas; McKendrick, Kirsty; Browne, John; Croudace, Tim; Barkham, Michael
Abstract : Background: Outcome measures for mental health services need to adopt a service-user recovery focus. Aims: To develop and validate a 10- and 20-item self-report recovery-focused quality of life outcome measure named Recovering Quality of Life (ReQoL). Method: Qualitative methods for item development and initial testing, and quantitative methods for item reduction and scale construction were used. Data from >6500 service users were factor analysed and item response theory models employed to inform item selection. The measures were tested for reliability, validity and responsiveness. Results: ReQoL-10 and ReQoL-20 contain positively and negatively worded items covering seven themes: activity, hope, belonging and relationships, self-perception, well-being, autonomy, and physical health. Both versions achieved acceptable internal consistency, test–retest reliability (>0.85), known-group differences, convergence with related measures, and were responsive over time (standardised response mean (SRM) > 0.4). They performed marginally better than the Short Warwick-Edinburgh Mental Well-being Scale and markedly better than the EQ-5D. Conclusions: Both versions are appropriate for measuring service-user recovery-focused quality of life outcomes. Declaration of interest: M.B. and J.Co. were members of the research group that developed the Clinical Outcomes in Routine Evaluation (CORE) outcome measures.